Influence of sense of coherence on adolescents’ self-perceived dental aesthetics; a cross-sectional study - Aline Cavalcanti da Costa; Fabrícia Soares Rodrigues; Priscila Prosini da Fonte; Aronita Rosenblatt; Nicola Patricia Thérèse Innes; Mônica Vilela Heimer (BMC Oral Health, 2017)
Abstract Background Sense of coherence (SOC) is a psychosocial factor capable of influencing perception of health, improving one’s ability to manage life. It is the central construct of salutogenesis. SOC allows for identification and mobilization of resources to effectively manage or solve problems, promoting health and quality of life. Using Wilson-Cleary’s conceptual model we hypothesized that SOC might contribute to self-perception of dental aesthetics. The aim of this study was to investigate whether SOC levels were related to self-perception of dental aesthetics against assessed normative orthodontic treatment need among adolescents. Methods A cross-sectional study was conducted with 615 male and female adolescents aged 12 to 15 years. Data collection comprised socio-demographic and socio-economic characteristics, SOC (SOC 13), self-perceived dental aesthetics (Oral Aesthetic Subjective Impact Scale), and assessment of orthodontic treatment need (Dental Aesthetic Index). Statistical analysis involved Pearson’s chi-square test, Kruskal-Wallis test, Mann-Whitney test and multiple linear regression. Spearman’s correlation coefficient was calculated for the determination of the strength of correlations among the numerical variables. The level of significance was set at 5% (p < 0.05). Results 50.1% of the participants were classified as having a high SOC (≥ median). Overall, SOC was associated with self-perceived dental aesthetics (p = 0.048). In the adolescents with no orthodontic treatment need, those with a low SOC perceived their dental aesthetics more negatively than those with high levels of SOC. The multiple regression analysis demonstrated an inverse relationship between SOC and: 1) age (p = 0.007), SOC being higher in the younger age group; 2) self-perceived dental aesthetics (p = 0.001), a higher SOC being associated with those who had a positive dental self-perception. Conclusions SOC was associated with self-perceived dental aesthetics and adolescents with a high SOC were more likely to perceive their dental aesthetics more positively. SOC did not seem to influence self-perception of dental aesthetics in adolescents who were clinically assessed as having an orthodontic treatment need, however, in those where there was no orthodontic treatment need, a low SOC was associated with a negative self-perception of dental appearance.